PENINGKATAN KUALITAS PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN JARING LABA-LABA SISWA KELAS IV SDN NGIJO 01, KECAMATAN GUNUNGPATI, SEMARANG THE IMPROVEMENT QUALITY OF SOCIAL STUDIES BY WEBBED MODEL AT CLASS OF IV NGIJO 01 ELEMENTARY SCHOOL, DISTRICT OF - Hermawan, Redi (KREATIF, 2011)
This Research background is the lower quality of Social Study to comprehend blind map of Central Java Province. ItÃ¢â¬â¢s caused by predominate teacher in the class; way of teacher submit separated items; lack of managing class; and lack of giving reinforcement to student. The impact which emerge ability of student does not expand, student quickly go against the stomach, and not enthusiastic in learning in Social Studies. This condition is still happened in class of IV Ngijo 01 elementary school, District of Gunungpati, Semarang. Target of this research are (1) To describe the improvement of teacher skill in comprehend blind map of Central Java Province; (2) To describe the improvement of student activities of Grade IV Ngijo 01 elementary school, District of Gunungpati, Semarang, in comprehending blind map of Central Java Province; (3) To improve student result learn of grade IV Ngijo 01 elementary school, District of Gunungpati, Semarang, in comprehending blind map of Central Java Province. The researcher uses a collecting data technique, that is observation, test, documentation, enquette, interview, and field note. The subject of the research are 29 students and teacher of grade IV. From the research which have been done, hence, there is an improvement of teacher skill value, the following: amount of cycle score of I is 20 with value of B, cycle of II is 25 with value of A, and cycle of III is 29 with value A. While, the improvement of student activities, the following: cycle score mean of I is 10,25 with value of C, cycle of II is 14 with value of B, and cycle of III is 16,8 with value of A. Result learn to mount, from cycle of I equal to 41%, cycle of II equal to 86%, and cycle of III equal to 90%. The conclusion of this research are (1) improvement of teacher skill in comprehend blind map of Central Java ProvinceÃÂ  by webbed model (2) the improvement of student activities of Grade IV Ngijo 01 elementary school, District of Gunungpati, Semarang, in comprehending blind map of Central Java Province by webbed model (3) the improvement of student result learn, in comprehending blind map of Central Java Province by webbed model. Researcher suggest the teacher to change the paradigm that webbed model just for applied in low class, because webbed model also can improve the quality of Social study in high class in comprehending blind map of Central Java Province. Key words: social study, webbed model, integrated learning